(untitled) (Indian Journal of Public Health Research & Development, 2025)
Background: Tuberculosis (TB), caused by Mycobacterium tuberculosis is a leading global infectious disease and remains a major health challenge despite advances in diagnosis and treatment. A total of 1.3 million people died from TB in 2022. India, with a high TB burden, launched the National Tuberculosis Elimination Program (NTEP) in 2020, transitioning from earlier control strategies to focus on TB elimination by 2025. This study aimed to assess the implementation of differentiated TB care guidelines in Banda district and to enhance patient outcomes and march towards India’s goal of TB eradication. Aim & Objective: To assess the preparedness of public health facilities for implementation of differentiated care of tuberculosis patients. Settings and Design: Cross-sectional study. Statistical analysis used: MS Excel, Jamovi software. Results: The assessment of TB care in Banda district revealed that Community Health Centers (CHC’s) offered essential treatments and diagnostic tools, but only 22% CHC’s had renal function tests and 33% CHC’s had liver function tests facility, and none had blood culture facility. The District Hospital, on the other hand, provided all necessary diagnostics and therapeutics but advanced surgical services were missing. Addressing these gaps is essential for improving TB care in the district. Conclusions: Despite availability of resource at CHC’s and District hospitals, gaps in tuberculosis care, including shortages in diagnostics, and anti-tubercular drugs, should be addressed. Improved training, coordination, and private sector engagement are essential for effective DTC implementation in Banda district. Key Messages: The "Differentiated Care of TB Patients approach focuses on individualized care by assessing TB patients through clinical, laboratory, and radiological evaluations. Using a risk stratification scoring system, it prioritizes patient-centered care to address risk factors, aiming to significantly reduce preventable TB-related deaths.